Guidelines for Urban Quality Assessment to Uplift Sustainable development of the Built Environment. Case Study of AL Rehab Neighborhood. Issue 1 (1st December 2022) - Sleem, S; Mandour, A; Diab, M
Abstract: A high-quality built environment is an urban environment that is bound to grow healthy and strong in the turmoil of time and crisis. Egyptian society had always been one that holds values that create a strong urban built environment strongly social and engulfed with the unbreakable bonds of culture and history. But there have never been the proper assessment guidelines for urban quality elements to aid an integrated fully functional sustainable development plan. This research paper presents guidelines for urban quality assessment to uplift sustainable development. Developing countries are in desperate need of new techniques to improve the quality of their urban quality, the lives of people drastically change when they feel like one with their community. The culture and personal needs of the Egyptian urban community should be taken into consideration to improve the quality of urban life.